Strong polar vortex favoured intense Northern European storminess in February 2022 - Ryan S. Williams; Amanda C. Maycock; Vincent Charnay; Jeff Knight; Inna Polichtchouk (Communications Earth & Environment)
Abstract February 2022 was an unusually stormy month over Northern Europe, including three extratropical cyclones impacting the United Kingdom and Ireland within a single week. The month also experienced an exceptionally strong stratospheric polar vortex; however, the role of this in preconditioning the risk of extratropical cyclone hazards has not been explored. Here we use constrained subseasonal forecasts to isolate the effect of the strong stratospheric polar vortex on the North Atlantic storm track in February 2022. We estimate the strong polar vortex led to a 1.5-3-fold increase in the likelihood of a cyclone with comparable intensity to the most intense storm that impacted the United Kingdom. We also show an increased likelihood of 3 or more storms reaching the United Kingdom in a single week by ~80% compared to if the polar vortex had been of average intensity. Using a storm severity index, we estimate a 3-4-fold increase in wind gust hazards over Scandinavia and Scotland and increases in monthly precipitation over Scotland, northern England and Ireland, and Scandinavia. The results show that the strengthened stratospheric polar vortex enhanced the risk of extreme North Atlantic extratropical cyclones, serial cyclone clustering, and their associated impacts over northern Europe in February 2022.